Discussing limb development and regeneration in Barcelona: The future is at hand. Issue 2 (12th November 2019) - Rosello‐Diez, Alberto; Whited, Jessica L.
Key Findings: Limb Development. Limb Regeneration. EMBO Barcelona Meeting.